Description of a new genus for Euptychia hilara (C. Felder & R. Felder, 1867) (Lepidoptera: Nymphalidae: Satyrinae) - Nakahara, Shinichi; Janzen, Daniel H.; Hallwachs, Winnie; Espeland, Marianne (Zootaxa, 2015)
Based on external morphology, food plant records for caterpillars, and molecular analysis, Euptychia hilara (C. Felder & R. Felder, 1867) is removed from Euptychia Hübner 1818. A new genus, Inbio Nakahara & Espeland gen. nov., is proposed for this taxon. Inbio hilara comb. nov. is a member of a monophyletic clade containing Cyllopsis Felder, 1869, Paramacera Butler, 1868, and Atlanteuptychia Freitas, Barbosa & Mielke, 2013, although it can be morphologically distinguished from these genera. Lectotypes for Neonympha hilara C. Felder & R. Felder, 1867 and Euptychia anacleta Butler, 1877 (a synonym of E. hilara) are designated herein.